CRIMINAL LEGAL PROTECTION OF LIFE OF A NEWBORN BABY - Yuri Alexandrovich Govenko (Science and Innovation Center Publishing House, 2016)
Crimes against life are very different from other types of crime by being a public danger: they lead to such consequences that cannot be repaired or reimbursed – the loss of life is irreversible. The harm is not limited only by the fact of death and hard moral consequences to relatives, but the state and society are also damaged because relatives lose help and society and state lose labor contribution of the citizen. That’s why Art.20 of Constitution of Russia allows death penalty for the most serious crimes against life as an exceptional measure of punishment (it includes Ch.2 Art 105 of Criminal Code of the Russian Federation). This article made a research of the criminal law protection of the newborn child’s life (Art.106 of the CC of RF) under mitigating circumstances and the problems of improving the criminal legislation, and realization of proposals aiming the improving of the criminal legislation will provide certainty of criminal responsibility for mothers who kill their newborn children; and also the differentiation of the criminal prosecution for women who decided to get rid of the child long before birth, and the murder itself was calmly planned act; and those women who killed their newborn children being in a traumatic situation or in a state of mental disorder not excluding sanity. The goal is to analyze the current legislation of law enforcement in the field of protection of the right to life of the newborn. The methodological basis of the article is the dialectic-materialistical method of cognition and comprehensive approach derived from it including elements of a system-information analysis. The results obtained during research are focused on practical application in the field of protection of newborn life. Application of results: the results are useful for improving the criminal legislation.